2021
DOI: 10.3390/pr9020390
|View full text |Cite
|
Sign up to set email alerts
|

Effective Desulfurization and Alumina Digestion of High-Sulfur Bauxite by New Roasting Process with Conveying Bed

Abstract: A new roasting process with a conveying bed was constructed and used to remove sulfur of high-sulfur bauxite. Roasting temperature, phase transformation, microcrystal, specific surface area of high-sulfur bauxite, and the mechanism of the reaction during the roasting process were analyzed. The digestion properties of roasted bauxite were also investigated. The results showed that the sulfur in high-sulfur bauxite can be efficiently removed by roasting in the conveying bed at 520‒720 °C for 2 s. Major reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The average alumina content is 68%, the aluminum-to-silicon ratio can reach 8, and the average sulfur content is 0.7% in high-sulfur bauxite, which is very suitable for the Bayer alumina production and has a high economic development value. , The study found that the sulfur of high-sulfur bauxite is mainly in the form of pyrite (FeS 2 ) . During the dissolution process of the Bayer production, S 2 2– , S 2– , and S 2 O 3 2– are mainly formed by 80% of pyrite reacting with alkali liquor. , These low-priced sulfur forms cause corrosion to equipment materials and other hazards to production processes. , At present, part of the dissolution equipment is made of stainless steel, while other tanks are mainly made of the traditional carbon steel in the production process of Bayer alumina in China. , With the recycling of alumina production, it is found that the steel has serious selective corrosion, pitting corrosion, corrosion cracking, and uniform corrosion. , In the production process of Bayer alumina, the different alumina production processes need to be completed at different temperatures, for example, the seed crystal decomposition temperature is 65 °C, the evaporation temperature is 110 °C, and the dilution temperature is 95 °C, approximately . Therefore, the study of the corrosion behavior of corrosion temperature on the tank material is of great significance to material protection and material selection.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The average alumina content is 68%, the aluminum-to-silicon ratio can reach 8, and the average sulfur content is 0.7% in high-sulfur bauxite, which is very suitable for the Bayer alumina production and has a high economic development value. , The study found that the sulfur of high-sulfur bauxite is mainly in the form of pyrite (FeS 2 ) . During the dissolution process of the Bayer production, S 2 2– , S 2– , and S 2 O 3 2– are mainly formed by 80% of pyrite reacting with alkali liquor. , These low-priced sulfur forms cause corrosion to equipment materials and other hazards to production processes. , At present, part of the dissolution equipment is made of stainless steel, while other tanks are mainly made of the traditional carbon steel in the production process of Bayer alumina in China. , With the recycling of alumina production, it is found that the steel has serious selective corrosion, pitting corrosion, corrosion cracking, and uniform corrosion. , In the production process of Bayer alumina, the different alumina production processes need to be completed at different temperatures, for example, the seed crystal decomposition temperature is 65 °C, the evaporation temperature is 110 °C, and the dilution temperature is 95 °C, approximately . Therefore, the study of the corrosion behavior of corrosion temperature on the tank material is of great significance to material protection and material selection.…”
Section: Introductionmentioning
confidence: 88%
“…The average alumina content is 68%, the aluminum-to-silicon ratio can reach 8, and the average sulfur content is 0.7% in highsulfur bauxite, which is very suitable for the Bayer alumina production and has a high economic development value. 3,4 The study found that the sulfur of high-sulfur bauxite is mainly in the form of pyrite (FeS 2 ). 5 During the dissolution process of the Bayer production, S 2 2− , S 2− , and S 2 O 3 2− are mainly formed by 80% of pyrite reacting with alkali liquor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to BP's "2020World Energy Statistical Yearbook", the global coal-fired power generation in 2019 was accounting for 27% of the total global power generation [2]. Sulfur is one of the harmful elements that will combine with oxygen and release sulfur oxides during combustion [3]. These sulfur oxides contribute to particulate matter (PM) and acid rain can affect human health and the environment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Sulfurous emission is one of the main sources of coal combustion pollution. Disulfide is formed during combustion of sulfur components contributing to particulate matter (PM) and acid rain, which causes damage to the environment and human health. , Therefore, coal desulfurization before combustion could make a unique contribution to environmental protection and the efficient use of coal resources.…”
Section: Introductionmentioning
confidence: 99%